Analisis Semiotika Puisi “Hatiku Selembar Daun” Karya Sapardi Djoko Damono (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Poetry is one type of literary work that has the deepest literary statement. The words that are raised contain deep understanding and are full of symbols. Reading poetry is a pleasure of literary art because the reader is brought along into the statements that a poet pours out through the lines of his poem. In the Big Dictionary Indonesian it is stated that poetry is a variety of literature whose language is bound by rhythm, matra, rhyme, and the arrangement of arrays and couplets.1Rahmat Djoko Pradopo gives the definition of poetry as a bound essay. The limitations of the poem are based on the attachment to (1) Many lines in each stanza, (2) Many words in each line, (3) Many syllables in each line, (4) Rhyme, and (5) Rhythm. Researchers are interested in conducting research on analyzing a poem by Sapardi Djoko Damono entitled "Hatiku Selembar Daun" by applying it through a semiotic approach. Semiotics is an analytical method used to explore the meaning contained in a sign. According to Susanne Langer "judging symbols or signs is important, animal life is mediated through feelings, but human feelings are mediated by concepts, symbols, and language." Semiotics is the study of how to give meaning to a sign. Semiotics can also be interpreted as the concept of teaching humans to interpret the signs that exist on a particular object. After going through the process of discussing the poem and paying attention semiotically, you will know about the meaning and linguistic signs contained in the poem Hatiku Selembar Daun so that it is conveyed to the reader.